RBOHD, GLR3.3, and GLR3.6 cooperatively control wounding hypocotyl-induced systemic Ca2+ signals, jasmonic acid, and glucosinolates in Arabidopsis leaves - Che Zhan; Na Xue; Zhongxiang Su; Tianyin Zheng; Jianqiang Wu (Plant Diversity, 2025)
Ca2+ signaling plays crucial roles in plant stress responses, including defense against insects. To counteract insect feeding, different parts of a plant deploy systemic signaling to communicate and coordinate defense responses, but little is known about the underlying mechanisms. In this study, micrografting, in vivo imaging of Ca2+ and reactive oxygen species (ROS), quantification of jasmonic acid (JA) and defensive metabolites, and bioassay were used to study how Arabidopsis seedlings regulate systemic responses in leaves after hypocotyls are wounded. We show that wounding hypocotyls rapidly activated both Ca2+ and ROS signals in leaves. RBOHD, which functions to produce ROS, along with two glutamate receptors GLR3.3 and GLR3.6, but not individually RBOHD or GLR3.3 and GLR3.6, in hypocotyls regulate the dynamics of systemic Ca2+ signals in leaves. In line with the systemic Ca2+ signals, after wounding hypocotyl, RBOHD, GLR3.3, and GLR3.6 in hypocotyl also cooperatively regulate the transcriptome, hormone jasmonic acid, and defensive secondary metabolites in leaves of Arabidopsis seedlings, thus controlling the systemic resistance to insects. Unlike leaf-to-leaf systemic signaling, this study reveals the unique regulation of wounding-induced hypocotyl-to-leaf systemic signaling and sheds new light on how different plant organs use complex signaling pathways to modulate defense responses.